Research progress on extraction and analytical methods for saxitoxin and its congeners - Ishak, Siti Munirah; Yahaya, Noorfatimah; Loh, Saw Hong; Kamaruzaman, Sazlinda; Mohamad Zain, Nur Nadhirah; Waras, Maisarah Nasution; Wan Abdullah, Wan Nazwanie; Miskam, Mazidatulakmam; Raoov, Muggundha; Abd Aziz, Noorizan; Hassan, Yahaya (Springer Science and Business Media LLC, 2023)
Saxitoxin is a potent neurotoxin commonly found in shellfish, produced by dinoflagellate and cyanobacterial blooms in seawater or fresh water. This review dissects the conventional liquid–liquid extraction (LLE) and solid-phase extraction (SPE) and the emerging microscale sample preparation method, followed by their achievements in the preconcentration of saxitoxin-group toxins from different matrices. Despite the tedious and multi-step procedures, LLE and SPE remain the most applied techniques in detecting saxitoxin due to their high sensitivity and selectivity. Nevertheless, microscale sample preparation offers potential as a green technique, especially in the development of advanced adsorbents for better sensitivity.